2007
DOI: 10.1176/appi.ajp.2007.06081358
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive and Negative Symptoms in Schizophrenia Trial (CONSIST): The Efficacy of Glutamatergic Agents for Negative Symptoms and Cognitive Impairments

Abstract: The study results suggest that neither glycine nor D-cycloserine is a generally effective therapeutic option for treating negative symptoms or cognitive impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
248
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(258 citation statements)
references
References 48 publications
3
248
1
6
Order By: Relevance
“…However, such positive findings have not always been reproduced (Buchanan et al, 2007). In fact, Roche recently stopped trials testing a GlyT-1 inhibitor for the improvement of negative symptoms in schizophrenia, perhaps due in part to the sole reliance on clinical rating scales rather than objective translational laboratory tests as primary outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…However, such positive findings have not always been reproduced (Buchanan et al, 2007). In fact, Roche recently stopped trials testing a GlyT-1 inhibitor for the improvement of negative symptoms in schizophrenia, perhaps due in part to the sole reliance on clinical rating scales rather than objective translational laboratory tests as primary outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Their activation follows the binding of glutamate once the D‐serine or glycine co‐agonists engage the specific allosteric site of the receptor (Kim et al., 2005). These two ligands were used in a clinical study on patients with severe schizophrenia as antipsychotic agents and were able to correct some negative clinical aspects (Buchanan et al., 2007). In 1991, Haring et al.…”
Section: Reviewmentioning
confidence: 99%
“…Exogenous glutamate leads to nervous system damage, therefore research primarily focused on targeting the glycine site (Olney 1990;Tsai et al 1999;Tsai and Coyle 2002;Tsai et al 2006). Although co-administration of glycine with ongoing antipsychotic treatment reduced symptoms in patients even after its discontinuation, these improvements were inconsistent (Evins et al 2000;Javitt et al 2001;Heresco-Levy et al 2004;Buchanan et al 2007). A meta-analysis of 18 short-term trials found that D-serine or glycine, NMDA receptor agonists to the glycine site, reduced the negative symptoms of schizophrenia but the results were inconsistent and the findings were inconclusive.…”
Section: Alleviation Of the Cognitive Symptomsmentioning
confidence: 99%